Theological Responses to the Concepts of Democracy and Human Rights: The Case of Contemporary Indonesian Muslim Intellectuals - Abdillah, Masykuri (Studia Islamika, 1996)
Almost all governments in the world, including authoritarian, claiming that their political system is democratic. However, not all governments in the Muslim world accept this system. Among the 'ulama and Muslim intellectuals themselves there are differences of opinion about the system and the concept of democracy. In general, the modernist Muslim groups accept this system, because he was judged to be compatible with Islam, while Muslim groups "fundamentalist" and mostly conservative Muslims reject this system, because it supposedly excludes the sovereignty of God.The problem that often arises is how to implement human rights in Islamic societies. Then in 1990 the Muslim countries which are members of the Organization of the Islamic Conference (OIC) issued a "Cairo Declaration of Human Rights in Islam" , after over 13 years of discussing this issue among its members. Thus, there are two declarations for the people of Islam, namely: Cairo Declaration on the top and the "Universal Declaration of Human Rights".DOI: 10.15408/sdi.v3i1.812